Nitrogen Doped Titania-Phosphorylated Chitosan For The Photocatalytic Decontamination Of Synthetic Dyes - Subramaniam, Sumaliny (2024)
The aim of this research is to develop a novel bifunctional photocatalyst composed of nitrogen-doped titania (N-doped TiO2) and phosphorylated chitosan (PCS) nanocomposite for the removal of Acid Red 88 (AR 88) and Methylene Blue (MB) from aqueous solutions. Phosphorylation of chitosan was successfully modified through solvothermal treatment using phosphoric acid in a closed Teflon-lined stainless-steel autoclave. Subsequently, the obtained PCS was incorporated with N-doped TiO2 to synthesize the N-doped TiO2-phosphorylated chitosan (NTP) nanocomposite via solvothermal treatment. The synthesized photocatalyst was thoroughly characterized using various analytical techniques, including scanning electron microscopy with electron dispersive X-ray spectroscopy (SEM-EDX), Fourier-transform infrared spectroscopy (FTIR), UV–Vis diffuse reflectance spectroscopy (UV-Vis DRS), Brunauer-Emmett-Teller (BET) analysis, X-ray diffraction analysis (XRD), X-ray photoelectron spectroscopy (XPS), and thermogravimetric analysis (TGA). Results indicated that the nanocomposite exhibited enhanced surface area and functional groups. The photocatalytic activity of NTP towards MB and AR 88 dyes were best described by the Langmuir-Hinshelwood kinetic model.